Islamic Banks in Morocco: Facts and Challenges - Fakhri, Lamiae; Lazrak, Yassir; Trid, Sabah (MALIA: Journal of Islamic Banking and Finance, 2023)
Though the global financial crisis has strongly challenged the development models of conventional finance, currently the participatory financial industry, known as "Islamic Banking", is systematically becoming important in several countries. In Morocco, many citizens wish to invest in these banks to avoid ‘Riba’, which is forbidden by the precepts of the Muslim Sharia. However, the instruments of Islamic banks are limited in terms of insurance and taxation, which makes them more exposed to risk. The objective of this research, therefore, is to shed light on both the situation of this industry since its emergence in Morocco and on the factors which prevent the advancement of participatory products in Morocco as well. The research concludes that numerous challenges face the Islamic financial industry, including strict Shariah compliance, regulatory and prudential challenges, competition, lack of awareness of Islamic finance, lack of uniform reporting standards, complexity of regulatory and supervisory issues, lack of consensus among Shariah scholars, and the absence of a centralized supervisory body. However, despite these challenges, the Islamic financial industry is growing steadily around the world and is increasingly accepted for its potential benefits, including financing Morocco's priority sectors, banking the population and promoting social solidarity through the establishment of ‘Zakat’ funds. To closely examine these two points, the present article adopts a systematic literature review method, which is a review of existing literature.